EXTERNAL MAGNETIC-PULSE STRAIGHTENING OF CARS BODY PANELS - Hnatov, A.; Гнатов, А. В. (Харьковский национальный автомобильно-дорожный университет, 2014)
The basics of magnetic-pulse attraction of both ferromagnetic and non-ferromagnetic thin-wall sheet metals are investigated. The design models of inductor systems-magnetic-pulse straightening tools are presented. The final analytical expressins for excited efforts design in the tools under consideration are introduced. The practical testing of magnetic-pulse straightening with the tools under study is given
ЗОВНІШНЄ МАГНІТНО-ІМПУЛЬСНЕ РИХТУВАННЯ КУЗОВНИХ ПАНЕЛЕЙ АВТОМОБІЛІВ
ВНЕШНЯЯ МАГНИТНО-ИМПУЛЬСНАЯ РИХТОВКА КУЗОВНЫХ ПАНЕЛЕЙ АВТОМОБИЛЕЙ
Keywords: external straightening; removal of dents; body repair; magnetic-pulse metal processing; car body panels; зовнішнє рихтування; видалення вм’ятин; кузовний ремонт; магнітно-імпульсна обробка металів; кузовна панель; внешняя рихтовка; удаление вмятин; кузовной ремонт; магнитно-импульсная обработка металлов; кузовная панель; 621.318